AMTRAK IN PERSPECTIVE: WHERE GOEST THE POINTLESS ARROW? - Patton, Edwin P (American Economic Review, 1974)
This paper considers Amtrak from an economic viewpoint. It analyzes Amtrak's markets and determines that there are two: corridors and long distance routes. It suggests criteria for evaluating Amtrak performance. It finds no case for subsidizing the long distance trains, but does cite circumstances under which corridor operations would be deserving of subsidies.